2014
DOI: 10.1111/1471-0528.12579
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive prenatal testing for trisomy 21: a cross‐sectional survey of service users' views and likely uptake

Abstract: Objective To assess the views and likely uptake of non-invasive prenatal testing (NIPT) for trisomy 21 among potential service users in the UK.Design Cross-sectional survey.Setting Four antenatal clinics in England and two websites.Sample A total of 1131 women and partners.Methods Questionnaire conducted with women (and partners) recruited through antenatal clinics, a random sample of members of the website Mumsnet, and viewers of the website and Facebook page of the support group Antenatal Results and Choices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
112
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(131 citation statements)
references
References 48 publications
(61 reference statements)
14
112
3
2
Order By: Relevance
“…Implementation into state funded healthcare systems requires further information to determine where it fits in the care pathway, what the uptake might be in clinical practice, whether the rate of invasive testing will change and if so how this might impact on service provision and training, the costs for the public health service and for service users, and how best to educate women and health professionals to ensure that informed choice is maintained. There is information available to address some of these issues, but it is largely based on studies assessing patient and health care views based on hypothetical scenarios in which indications are that uptake will be high (Sayres et al 2011;Tischler et al 2011;Hill et al 2012a;Lewis et al 2013Lewis et al , 2014a or modeled data to inform discussions on potential economic impact Beulen et al 2014;Morris et al 2014). However, it is well documented that what happens in clinical practice does not always reflect what people say/believe they will do hypothetically.…”
Section: Implementation Of Nipt For Aneuploidy Into Public Sector Heamentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation into state funded healthcare systems requires further information to determine where it fits in the care pathway, what the uptake might be in clinical practice, whether the rate of invasive testing will change and if so how this might impact on service provision and training, the costs for the public health service and for service users, and how best to educate women and health professionals to ensure that informed choice is maintained. There is information available to address some of these issues, but it is largely based on studies assessing patient and health care views based on hypothetical scenarios in which indications are that uptake will be high (Sayres et al 2011;Tischler et al 2011;Hill et al 2012a;Lewis et al 2013Lewis et al , 2014a or modeled data to inform discussions on potential economic impact Beulen et al 2014;Morris et al 2014). However, it is well documented that what happens in clinical practice does not always reflect what people say/believe they will do hypothetically.…”
Section: Implementation Of Nipt For Aneuploidy Into Public Sector Heamentioning
confidence: 99%
“…Women value the improved safety secondary to the reduction in invasive testing as well as early, easy access to a highly sensitive test (Hill et al 2012a;Allyse et al 2014;Lewis et al 2014a;Sayres et al 2011) and health professionals value the improved accuracy of screening as well as the safety . Furthermore, studies based on hypothetical scenarios of offering NIPT have indicated that an additional group of women, who would decline current screening and diagnosis because of the risk of miscarriage, will undergo NIPT to plan and prepare for the birth of an affected child (Sayres et al 2011).…”
Section: Stakeholder Opinions and Educationmentioning
confidence: 99%
“…Sir, In our recent publication 1 we presented the results of a cross-sectional survey with 1301 women and partners and showed that service users are very positive towards the introduction of noninvasive prenatal testing (NIPT) for trisomy 21 and that uptake is likely to be high, although a small proportion would prefer invasive testing. Sala et al 2 suggest that pre-test counselling for survey participants would have resulted in a more accurate indication of test uptake.…”
Section: Authors' Replymentioning
confidence: 99%
“…Noninvasive prenatal testing for trisomy 21: when counselling is needed before responding to a survey Sir, Lewis et al 1 assess the views and likely take-up of noninvasive prenatal testing (NIPT) for trisomy 21 among potential service users in the UK, with potentially important implications for healthcare service providers. The analysis of questionnaires submitted to more than 1000 women suggests a positive view of the introduction of NIPT into prenatal care and that its take-up is likely to be high.…”
mentioning
confidence: 99%
“…In our recent publication 1 we presented the results of a cross-sectional survey with 1301 women and partners and showed that service users are very positive towards the introduction of noninvasive prenatal testing (NIPT) for trisomy 21 and that uptake is likely to be high, although a small proportion would prefer invasive testing. Sala et al 2 suggest that pre-test counselling for survey participants would have resulted in a more accurate indication of test uptake.…”
Section: Sirmentioning
confidence: 99%